An Example of Nationalist Historiography in Modern İran: Do Qarn Sokut - Ayşe Sosar (Şarkiyat Mecmuası)
Do Qarn Sokut(Two Centuries of Silence) is a work by Abdolhossein Zarrinkoub, a prominent figure in the intellectual life of 20th-century Iran, known for his roles as a literary figure and historian. It was written in 1330/1952 and encompasses events that occurred during the first two centuries of Islam, from the fall of the Sassanian Empire to the establishment of the Tahirids (205/821), the first independent state formed on Iranian soil after the advent of Islam. Zarrinkoub’s book provides a narrative of these events and the state of Iran during that period. Since its publication, the book has received considerable attention and has become a focus of intense scrutiny. It is one of the most discussed and debated works in Iranian history. Do Qarn Sokut represents a significant example of the Pahlavi era’s historical writing project and official historiography,embodying a secular nationalist image of Iranian history that elevates and sanctifies everything related to pre-Islamic Iran while denigrating aspects of the Islamic era. In this context, it is considered an essential contribution to the Iranian historical discourse. Within this study, emphasis is placed on the examination of the historical narrative presented in the book, not through a straightforward discussion of its alignment with historical realities and truths, nor through an evaluation of rejection or affirmation. This study delves into the purpose (ideological, political, and societal) behind the narrative in the book and how it has been shaped.